Design and development of polybenzoxazine-POSS hybrid materials from renewable starting materials for low k and low surface free energy applications. (23rd August 2019) - Devaraju, S; Krishnadevi, K; Naveena, E; Alagar, M
Abstract: The introduction of nano-sized polyhedral oligomeric silsesquioxane (POSS) derivatives into polymer matrices have received significant interest in recent years mainly because of the inherent properties of POSS which include low coefficient thermal expansion, low density, low thermal conductivity, low dielectric constant, high oxidation resistance, and low surface free energy. In view of this, an attempt has been made to develop thermally stable, flame retardant, low dielectric, and lower surface free energy polybenzoxazine-POSS (PBz-POSS) hybrid prepared using renewable agro-waste (cardanol, furfurylamine and stearylamine) as starting materials. A new approach involving thiol-ene click reaction has been adopted to introduce mercapto functional POSS (SH-POSS) into cardanol benzoxazines (Bz-C-F and Bz-C-S). The thermal, dielectric, flame-retardant, and contact angle studies of the prepared PBz-POSS hybrids were investigated using modern characterization techniques. The results from thermal, flame, dielectric and water contact angle studies clearly indicate that the developed renewable, cost-effective and eco-friendly PBz-POSS hybrid materials can be exploited as coatings and sealants as well as for low dielectric microelectronic applications to substitute the currently used petroleum-based raw materials.